Evaluasi Pelayanan Ambulans Hebat Kota Semarang: Inovasi dan Tantangan dalam Pelayanan Kesehatan Darurat - Lollyta Lollyta; Indra Kertati; Sumarmo Sumarmo (Jurnal Media Administrasi, 2025)
The purpose of this research is to analyze the innovation in emergency health services through the implementation of the Ambulans Hebat program in Semarang City, to analyze the challenges and obstacles faced in the implementation of the Ambulans Hebat service, and to analyze the quality of emergency health services provided by Ambulans Hebat. This research is descriptive qualitative in nature, using interview techniques with 9 informants and a questionnaire with 96 respondents. The results of this research show that the Ambulans Hebat program in Semarang City demonstrates innovation through digital technology (GPS, applications) that enhances response and coordination, an integrated command center for efficient information flow, and medical personnel training, although it requires better data integration, signal strengthening, and broader training; however, challenges such as limited fleet and medical personnel, weak inter-agency coordination, and traffic impacts necessitate additional units, integrated systems, and infrastructure innovations; quality evaluation indicates a 15-minute response time, high patient satisfaction, and successful initial handling, but requires route optimization, expanded satisfaction surveys, and additional technical training.